EFEKTIFITAS GERAK DAN LAGU “PERGI KE SEKOLAH” DALAM MENINGKATKAN KEMAMPUAN BAHASA ANAK USIA 5–6 TAHUN (Jurnal Tata Kelola Pendidikan, 2020)
The purpose of this study was to determine how effective the motion and song "Going ToSchool" in improving the language skills of children aged 5-6 years in TK Pertiwi BanaranKab. Nganjuk This research is a quantitative study with a pre-experimental design methodshowing that the motion and the song "Going to School" are effective for stimulatinglanguage skills of children aged 5-6 years in group B in TK Pertiwi Banaran Kab. NganjukThe number of samples in this study were 21 children. Pretest results with an average valueof 9.76, a maximum value of 14, and a minimum value of 5. While posttest results with anaverage value of 14.14, a maximum value of 20, and a minimum value of 4. Results of dataanalysis using Paired Test Sample T-Test with df = 20 shows a t table of 2.085 and a t-testvalue of 12.112. This shows t arithmetic> from the t table value so that the motion and thesong "Go to School" are effective in stimulating language skills of children aged 5-6 years.
Keywords: Effectivity; Language Skill; Motion and Song “Pergi Ke Sekolah”